IDENTIFIKASI DAN ANALISIS KONFLIK SOSIAL DI KABUPATEN BUTON - La Janu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study aims to identify and analyze social conflicts in Buton District, especially to get a picture of the identity of stakeholder involved either directly or indirectly in the conflict, the types of relationships of the stakeholder involved in the conflict, the various interests involved in the conflict, various issues who are involved in the conflict and who can be encouraged in conflict resolution. The data collection in this research is based on information from several sources, that is through online media, literature study, and field research, by observing the conflict incident and meeting the informant directly, then conducting the interview related to conflict incident. The collected data then analyzed as descriptive qualitative. The results of this study indicated that there were 6 social conflicts that occurred in Buton district in recent years and overall caused by conflict of interest in the form of satisfaction and the fulfillment of needs by sacrificing others, the control and monopoly of natural resources and environment, especially the uncertainty of land boundaries and problems land acquisition by the company. There are no casualties in the conflict because the scale is only limited to war of words or grandiosity. But before transforming into a large-scale conflict, they need efforts or actions to prevent, reduce, and even resolve the totality of the conflict to the roots. Keywords: identification, analyse, social conflict